Teaching police officers fairness: lessons from a field trial in the United Kingdom - Langley, Brandon (Springer, 2024)
This book explores the growing body of research associated with police legitimacy. It reports on a systematic review to trace, evaluate, and synthesize all the results of published police procedural justice training tests. Further, the volume explores, for the first time, the theoretical relationship between training on procedural justice and both officer self-legitimacy and audience legitimacy as outcomes within the context of counterterrorism policing. It evaluates a number of key topics, including: • The effect of police officers’ higher levels of self-legitimacy on how they conduct themselves. • The design, implementation, and management of a national test examining the effect of a bespoke procedural justice training package aimed at stimulating offices inner confidence. • Audience legitimacy scores in the sensitive world of counterterrorism policing. The chapters that follow explore legitimacy theory, procedural justice, and the lesser-known self-legitimacy component. This volume is ideal for law enforcement professionals, policymakers, criminal justice practitioners, and researchers involved in combating terrorism and improving police legitimacy.